Investigating secondary mathematics teachers’ self-efficacy beliefs, TPACK and challenges towards technology integration - Aguinaldo, Clemente M., Jr. (Animo Repository, 2020)
This study investigated the perceived self-efficacy beliefs towards technology integration and technological, pedagogical and content knowledge (TPACK-M) of high school mathematics teachers along with the challenges they encounter in integrating technology in their classrooms. Using a survey questionnaire, the respondents reported a moderately high self-efficacy beliefs and measures of knowledge in TPACK-M constructs with significant predictive relationship between these variables. The teachers differ in their beliefs and knowledge when grouped according to their gender but not by their age and years of teaching experience. The challenges they encountered include limited technology resources, poor or lack of internet connection, insufficient technological skills, power interruptions, and students’ unfavorable attitudes and inadequate computer skills. To ascertain the actualities of technology integration within school contexts, it is recommended that class observations and interviews will be done.